Use of Impulse Response Instrument in Concrete Pavement: A Review - Harle, Shrikant M; Pajgade, Prakash S (Journal of Asian Scientific Research, 2017)
In the concrete structure the defects like excessive honeycombing, crack in the structure, etc are the concerns to be noticed. Actually in most of the cases the defects are unable to find out but the soundings of the hammer is used to detect the locations of the delaminations. The evaluation of the concrete surface with the extensive surface cracking can be evaluated with the help of NDT test such as impulse response. The causes of the cracking can also be studied so that it can be avoided. The present study deals with the experimental investigations carried out by the different researchers.